2020
DOI: 10.1177/0003319720946971
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibitors Versus Angiotensin II Receptor Blockers in Acute Coronary Syndrome and Preserved Ventricular Ejection Fraction

Abstract: Angiotensin-converting enzyme inhibitor (ACEi) and angiotensin II receptor blockers (ARB) showed comparable survival results in patients with heart failure (HF) and reduced left ventricular ejection fraction (LVEF). However, there is lack of evidence of the comparative effectiveness in preserved LVEF patients after an acute coronary syndrome (ACS). The aim of this study was to evaluate whether the selection between ACEi and ARB in preserved LVEF after an ACS confers a prognostic benefit, based on real life res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Focusing on patients without impaired LVEF, the prognostic role of ACEi and ARB was comprehensively investigated in 3006 patients with acute coronary syndrome and preserved ejection fraction (i.e., LVEF ≥ 40%). A comparable risk of all-cause mortality, as well as similar rates of the composite endpoint (i.e., death, AMI and HF) were demonstrated in patients treated with ACEi as compared to ARB [ 21 ]. These comparable effects may rely on the comparable effect of ACEi and ARB reducing the synthesis of angiotensin II, which represents a cornerstone in the pathogenesis of arrhythmic events on a structural, cellular and electrophysiological level [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on patients without impaired LVEF, the prognostic role of ACEi and ARB was comprehensively investigated in 3006 patients with acute coronary syndrome and preserved ejection fraction (i.e., LVEF ≥ 40%). A comparable risk of all-cause mortality, as well as similar rates of the composite endpoint (i.e., death, AMI and HF) were demonstrated in patients treated with ACEi as compared to ARB [ 21 ]. These comparable effects may rely on the comparable effect of ACEi and ARB reducing the synthesis of angiotensin II, which represents a cornerstone in the pathogenesis of arrhythmic events on a structural, cellular and electrophysiological level [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, neither of the above study populations [18][19][20] were restricted to patients with UA.…”
Section: Discussionmentioning
confidence: 99%
“…After PSM, they found that the occurrence of allcause death (HR = 1.113, 95% CI: .986-1.257, P = .084) was not significantly different in the angina group, with a median follow-up of 2.2 years. Nevertheless, neither of the above study populations [24][25][26] were restricted to patients with UA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACEI/ARB has been shown to reduce adverse cardiovascular events in patients with HF, MI combined with HF, and high-risk CAD ( 20 22 ). In the HOPE study, ramipril significantly reduced the rates of composite endpoints of death from a cardiovascular cause, MI, and stroke in high-risk patients who are not identified as a low LVEF or HF ( 20 ).…”
Section: Discussionmentioning
confidence: 99%